USING ONLINE STUDENTS RESPONSE SYSTEM PLATFORMS AS INTEGRATING TECHNOLOGY ON ENGLISH FOR MANAGEMENT LEARNERS’ READING COMPREHENSION. - Iswatin, iswatin (Journal of English Teaching, Literature, and Applied Linguistics; Vol 4 No 2 (2020), 2020)
Teaching reading not only reads the literature but also comprehends the text, including in teaching ESP reading. Several issues in teaching ESP reading comprehension can be barrier for the success of the teaching and learning process which needs to integrate technology such as smartphone that come up as media to make teaching strategy run well. Online Students Response Systems platform via smartphone can be one of alternatives for teaching reading. This study was aimed to know the effect of Students Response Systems using (Kahoot! and Socrative) toward English for Management students reading comprehension. D1 Equivalent English program students was engaged, 37 (7 males and 30 females) from Management students of A-class as treatment group while control group from B class consisted of 38 students (6 males and 32 females). Quantitative quasi experimental and descriptive quantitative survey as the designs of this study. Pre and posttest as the first instrument analyzed by using T-test while Likert-scale questionnaire as the second instrument analyzed to find the frequencies and percentages. The result shows that the increasing correlation between pre-test and post-test in treatment group is 64,1%, while the increasing correlation between pretest and post-test in control group is 30,8%. The post-test scores of both two groups in Independent T-test showed significant difference improvement with the score of Sig. is 0,670 > 0,05 and the score in “equal variances assumed” showed that significance 2 tail (t-tailed) is 0.000 < 0.05. From that result, teaching using SRS (Kahoot! and Socrative) is effective for enhancing Management learners’ reading comprehension. The students’ perspectives related to the SRS (Kahoot! and Socrative) usage is dominated by positive perceptions’ statement of agree and strongly agree. However, this study found factor that necessary to be consideration that is accommodating the time management.